2015
DOI: 10.1109/jlt.2015.2395537
|View full text |Cite
|
Sign up to set email alerts
|

Coherent Plasmonic Interconnection in Silicon-Based Electrical Circuit

Abstract: This paper presents a feasibility study of optical interconnections using surface plasmon polaritons (SPPs) as coherent carrier waves in a silicon-based electrical circuit. A gold film plasmonic waveguide and a gold/silicon Schottky-type plasmonic detector were monolithically integrated with an electrical circuit based on metal-oxide-semiconductor field-effect transistors on a silicon substrate. A 1550-nm-band laser source was used for SPP excitation, and the photocurrent generated by the plasmonic detector wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…In addition to the plasmonic intensity signal transmission, coherent signal transmissions could be performed when highcoherence (i.e., narrow spectral linewidth) optical sources were used. We previously reported on the feasibility of coherent signal transmission through a plasmonic waveguide integrated metal-oxide-semiconductor field-effect transistors (MOSFETs) using a self-delayed homodyne technique [32], [33]. In those studies, we observed beat signals with a peak at 0 Hz outputted from a MOSFET.…”
Section: Figure 6 Spp Propagation Length On Au Surface As a Function Of Oscillation Frequency Based On The Drude Modelmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition to the plasmonic intensity signal transmission, coherent signal transmissions could be performed when highcoherence (i.e., narrow spectral linewidth) optical sources were used. We previously reported on the feasibility of coherent signal transmission through a plasmonic waveguide integrated metal-oxide-semiconductor field-effect transistors (MOSFETs) using a self-delayed homodyne technique [32], [33]. In those studies, we observed beat signals with a peak at 0 Hz outputted from a MOSFET.…”
Section: Figure 6 Spp Propagation Length On Au Surface As a Function Of Oscillation Frequency Based On The Drude Modelmentioning
confidence: 97%
“…In this technique, the transmitted signal intensity is amplified with the local oscillator via the beating. Using the optical heterodyne detection technique, the transmitted plasmonic signals have been amplified by approximately 14 dB by mixing the transmitted signals and the local oscillator [32].…”
Section: Signal Multiplexingmentioning
confidence: 99%
“…Ref. [89] has presented a gold/silicon based monolithic integrated circuit consisting of a gold film plasmonic waveguide. It is demonstrated that SPPs can be used as a coherent carrier in a circuit, capable of providing highly integrated optical interconnects for data processing applications.…”
Section: Pics Based On Spp Modesmentioning
confidence: 99%
“…Moreover, compared to silicon-based OPAs where a considerable part of power is emitted into the substrate layer 10 , 15 (the upward and downward emissions are at the same level), the proposed POPA is free of the energy leakage into the substrate side. These features make the proposed POPA a promising building block for plasmonic IC applications such as the construction of on-chip optical wireless nanolinks 22 , integrated plasmonic lasers 23 , 24 and nanoantenna couplers between photons and plasmonic integrated circuits 20 , 25 , 26 . Furthermore, considering the plasmonic nature of the proposed POPA, the influence of the delocalized surface plasmons 27 31 on the proposed POPA is investigated.…”
Section: Introductionmentioning
confidence: 99%